Uterocutaneous fistula managed medically: A case report. - Koulshan Mustafa; Gul-e-rana Abdul; Rabiya Niaz; Durr-e-shahwar Hayat; Sultan , Anum (International Journal of Endorsing Health Science Research, 2023)
Background: The uterocutaneous fistula is an abnormal connection or passageway between the uterus and the skin. The most common causes include infections, trauma, or surgery, a severe medical condition requiring prompt medical attention and treatment. Case Presentation: Here, we describe the case of a 36-year-old female who developed a uterocutaneous fistula after cesarean delivery. Her post-cesarean recovery was complicated by wound infection, and after healing the wound, she presented with cyclical bloody discharge from a pinpoint opening in the healed wound scar. Management: On ultrasound and MRI, she was diagnosed as having a uterocutaneous fistula. She opted for non-surgical management and underwent successful medical management with GnRH agonists. She remained symptom-free after the resumption of her menstrual cycle. Conclusion: In younger populations hoping to avoid surgery, pharmacological care with GnRH agonist therapy can be a reasonable alternative to surgical resection of the fistulous tract. Healthcare professionals should have a high index of suspicion to diagnose this condition.